Time Management for Department Chairs - Christian K Hansen (Academic Chairpersons Conference Proceedings, 2018)
Most department chairs face the challenge of getting important tasks completed under time constraints in an environment of frequent interruptions. Department leaders are often bombarded with demands from students, faculty and administrators and spend an excessive number of hours each day managing tasks that are often associated with tight deadlines. The nature of the chair position is likely to result in stress, burn out, and other unhealthy situations. This workshop presents strategies and proven practices for taking control of the available time and getting the job done while managing stress and giving priority to leading a healthy and enriching personal life. Key focus is on defining short-term and long-term goals, preparing "time budgets," managing priorities, and eliminating "time wasters."
Keywords: Time management; effectiveness; academic leadership; delegation; priorities; time budget; time-wasters; to-do-list.